Impact of Sacral Surface Therapeutic Electrical Stimulation on Early Recovery of Urinary Continence after Radical Retropubic Prostatectomy: A Pilot Study - Haruo Nakagawa; Yasuhiro Kaiho; Shunichi Namiki; Shigeto Ishidoya; Seiichi Saito; Yoichi Arai (Advances in Urology)
Objectives. To investigate whether sacral surface therapeutic electrical stimulation (SSTES) initiated during the early postoperative period would be effective towards early recovery of postprostatectomy urinary continence. Methods. A total of 35 consecutive patients who underwent radical prostatectomy by a single surgeon were enrolled in this study. Twenty early patients began pelvic floor muscle exercise (PME). Fifteen subsequent patients received SSTES postoperatively with no instruction for PME provided. Immediate urinary function just after catheter removal was evaluated with frequency-volume chart and 24-hour pad test. Results. There were no differences between the SSTES and PME groups in maximum voided volume capacity (MVV) and urine loss ratio (ULR) on the first day after removal of urethral catheter. However, on day 3 MVV was significantly larger and ULR was also significantly lower in the SSTES group. Conclusions. SSTES treatment is feasible and appears to be effective for early recovery of urinary continence after radical prostatectomy.